FACTORS INFLUENCING INDIAN FIRMS DECISION MAKING IN FOREIGN DIRECT INVESTMENT IN AFRICA - Mukta Kukreja; Dr. Mahesh Chandra Joshi (AIBPM Publisher, 2018)
India’s economic progress and relations with other developing regions have received much attention, particularly the way in which Indo-African relations have evolved since 2000. This paper aims to put Indian FDI in Africa into perspective and provide some answers on the nature and possible impact of these flows to the continent. The study utilized the international typology offered by Dunning OLI paradigm to identify the important of Location Specific Advantages and how these advantages leads to selection of location for investment purposes by investors The study findings demonstrated that potential market growth, market opportunities and consumer base are the important indicated Indian firms targets Africa to seek new and unexplored markets of Africa. Competitiveness climate is important determinant along with economies of scale, investment incentives and availability of natural resources.